Implementation of the 5s methodology in a teaching and research laboratory at a Federal University - Passos, Yslaine Rodrigues dos; Almeida, Karolinne de Araujo; Magalhães, Laurence Colares; Gomes, Thiara Cezana; Torres, Henrique Bertochi (Brazilian Journal of Production Engineering, 2025)
The 5S method, essential to Lean Manufacturing, promotes organization and continuous improvement. Recognizing its potential to mitigate challenges in the academic environment, this study implemented 5S in an Integrated Manufacturing Laboratory (IML) of a teaching and research institution, aiming to improve operationalization, safety, and efficiency. A nine-stage action research approach was adopted, including initial diagnosis, implementation of the sensors, and assessment of student and faculty satisfaction. The intervention demonstrated a significant improvement in the environment's compliance, which increased from 36% to 98% in the Seiri, Seiton, and Seiso sensors. Consequently, the IML became more organized, safe, and efficient. High student satisfaction (with averages above 4.50 on a 5.0 scale) validated the importance of the changes. The study demonstrates the effectiveness of 5S as a quality management tool in university laboratories, serving as a basis for other institutions to optimize their spaces and promote a culture of safety.
Keywords: Lean Manufacturing; 5S; Quality Management; Continuous Improvement